OCCLUDED GASES EFFECT ON ACOUSTIC EMISSION UNDER CRYSTAL SALVATION - Dmitry M. Kuznetsov; Petr N. Kozachenko; Olga O. Barannikova (Advanced Engineering Research)
The acoustic emission following the salt solution processes is investigated. It is educed that the acoustic emission parameters depend on the substance chemistry. It is stated that irrespective of the crystal purity degree with their dissolution the total count of signals increases logarithmically, and activity of the acoustic emission decreases exponentially. It is shown that the occluded gases liberation is a crucial element of the acoustic emission under the crystal dissolution.